D4.22 Human Resources Accreditation/Certification (Years 1-4) - Christofini, Anthia; Antoniou, Theofilos; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2023)
This deliverable focuses on the progress made regarding Eratosthenes CoE accreditation under the European Commission’s “HR Excellence in Research Award” and the effort made via the accreditation process to align Eratosthenes CoE human resources policies and practices with the 40 principles of the European Charter for Researchers and the Code of Conduct for the Recruitment of Researchers(hereinafter the “European Charter and Code”), based on a customized action plan and human resources strategy. Eratosthenes CoE, with a strong commitment to fostering a stimulating and high-quality environment for researchers, scientists, and support staff, is determined to pursue the prestigious "HR Excellence in Research Award." Recognizing the pivotal role that Human Resources/People Management plays in shaping the research landscape, Eratosthenes has integrated the EC "HR Strategy for Researchers" into its Human Resources Strategy. As a clear demonstration of its dedication to excellence, Eratosthenes, following the implementation phase, will diligently seek external assessment every three years to retain the "HR Excellence in Research Award." This effort is not merely about accolades; rather, it underscores Eratosthenes' profound commitment to elevating organizational performance, ensuring exceptional quality, and providing steadfast support for the professional growth and career development of its valued personnel. Through this pursuit, Eratosthenes aims to set a remarkable standard in the research community, cultivating an environment that empowers its members and advances the frontiers of knowledge. It is strongly believed that the changes that are made to Eratosthenes CoE human resources practices and policies, and relating to the obtainment of the HR Excellence in Research Award, will attract and retain international talent and make Eratosthenes an attractive employer for researchers.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; Human Resources